Facts about Niacin - R. Elaine Turner (EDIS, 2006)
Revised! FCS-8669, a 2-page fact sheet by R. Elaine Turner, has been updated with new graphics and revised figures for the amount of niacin in common foods. Published by the UF Department of Family Youth and Community Sciences, April 2006.